미취학아동의 1일 활동량, 활동계수 평가 및 유아보육시설의 실외놀이 실태 - 김재희(Jae Hee Kim); 김은경(Eun Kyung Kim) (Korean journal of community nutrition, 2009)
The purpose of this study was to assess physical activities and activity coefficient of preschool children and was to give some concrete information to activate outdoor play and to probe the suggestions to activate outdoor play. 42 preschool children (17 boys and 25 girls) were included. Body weight and height were measured and one-day activity diaries were collected by interviewing with their parents and kindergarten teachers. To measure physical activity during outdoor play, this study was researched the current conditions and content of outdoor play activity in daycare centers, and teacher's perceptions of that outdoor play. The average age of the subjects was 5.0 years. Average height, weight, body fat and body muscle of subjects were 108.9 cm, 18.9 kg, 17.7% and 26.8%, respectively. The subjects spent about 10 hours 39 minutes sleeping; 4 hours 16 minutes personal hygiene and computer working. They spent 88.2% of 24 hours (one day) in "very light activities" and 11.3% in "light activities". Activity coefficient (1.34) of weekday was significantly higher than that of weekend (1.21). And in this study, it was found that most of daycare centers (87.7%) have outdoor play space, 95.2% of them were garden. The teachers recognized that have a outdoor play frequency everyday (48%), three or four times (46%) in a week but they have three or four times (38%), one or two times (30%) because of various indoor program. Also, they recognized that have a outdoor play expending time 21-30 minutes (48%), 31-40 minutes (26%) but they have 21-30 minutes (64%). They answered that have frequency and expending time less than their recognition of outdoor play. Most of daycare center teachers perceived outdoor play to be as important as indoor play, and the teachers believed outdoor play supports children's physical, cognitive, social, and language development. The results of this study may be used to utilize as a basic data for estimate physical activity for preschool children and developed that exercise program to increase physical activity of daycare center outdoor play.